Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014 IEEE 11th International Symposium on Biomedical Imaging (ISBI) 2014
DOI: 10.1109/isbi.2014.6867976
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based evaluation of susceptibility distortion correction methods in diffusion MRI for connectivity analysis

Abstract: Connectivity analysis on diffusion MRI data of the wholebrain suffers from distortions caused by the standard echoplanar imaging acquisition strategies. These images show characteristic geometrical deformations and signal destruction that are an important drawback limiting the success of tractography algorithms.Several retrospective correction techniques are readily available. In this work, we use a digital phantom designed for the evaluation of connectivity pipelines. We subject the phantom to a "theoreticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 12 publications
(13 reference statements)
0
27
0
Order By: Relevance
“…Thus, the reader may wish to compare the relative performance of different distortion compensation methods in their own dataset, using an approach similar to ours. We used multiple metrics to quantify EPI-T1 agreement as a proxy for correction quality (i.e., Dice coefficients for whole-brain masks and CSF-excluded masks, as well as mutual information), since we acknowledge that there is no single gold standard for measuring the quality of distortion compensation in human brain imaging data 28 (but see the following studies that used simulations to try to establish ground truth 47,48 ). By making our data and analysis code publicly available (see Methods), we hope to facilitate the empirical selection of effective approaches for geometric distortion compensation in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the reader may wish to compare the relative performance of different distortion compensation methods in their own dataset, using an approach similar to ours. We used multiple metrics to quantify EPI-T1 agreement as a proxy for correction quality (i.e., Dice coefficients for whole-brain masks and CSF-excluded masks, as well as mutual information), since we acknowledge that there is no single gold standard for measuring the quality of distortion compensation in human brain imaging data 28 (but see the following studies that used simulations to try to establish ground truth 47,48 ). By making our data and analysis code publicly available (see Methods), we hope to facilitate the empirical selection of effective approaches for geometric distortion compensation in future research.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, previous work has generally shown better performance for oppPE field map strategies, as compared to B0 field maps, which has been attributed in part to the difficulty of using B0 field maps to correct distortion near the edges of the brain (see Figure 1F), where phase values change rapidly. Using simulated EPI data, both Esteban 47 and Graham 48 showed quantitatively that ground truth undistorted images were recovered best using an oppPE field map method, whereas B0 field maps performed slightly worse, and nonlinear registration-based methods were greatly inferior (but still better than no correction at all). Similar conclusions were reached by Hong and colleagues 28 using SE EPI in the mouse brain at 7T, by Holland and colleagues 34 using SE EPI at 1.5 and 3T in the human brain, and by Wang and colleagues 49 using 3T dMRI data in humans (see also 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is common to collect LR (left right) and RL (right left) images, or AP (anterior posterior) and PA (posterior anterior) images. Phase encoding based techniques have been demonstrated to outperform the other two approaches (Graham et al, 2017;Esteban et al, 2014), at the cost of a longer scan time.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of ground truth means that evaluations are typically indirect or qualitative (Jezzard and Balaban, 1995;Wu et al, 2008;Bhushan et al, 2012;Ruthotto et al, 2013;Fritz et al, 2014;Irfanoglu et al, 2015;Taylor et al, 2016;Hedouin et al, 2017;Wang et al, 2017;Irfanoglu et al, 2018). Only a few investigations have been carried out with the presence of a ground truth for evaluation of susceptibility distortion correction (Andersson et al, 2003;Esteban et al, 2014;Graham et al, 2017). Hedouin et al (2017) compared aDC, aBMDC and TOPUP using phantom data and human data.…”
Section: Introductionmentioning
confidence: 99%
“…Diffantom is originally designed for the investigation of susceptibility-derived distortions, a typical artifact that produces geometrical warping in certain regions of dMRI datasets. In Esteban et al (2014) we addressed this phenomenon and concluded that the connectivity matrix of 1 Available at: http://www.tractometer.org/ismrm_2015_challenge/.…”
Section: Introductionmentioning
confidence: 99%